Gig Economy Worker’s Legal Status: Employee or Independent Contractor? - Ni Kadek Ayu Sri Undari; Haruka Sugiyama (Focus Journal : Law Review, 2024)
The gig economy was born as a new economic scheme due to technological disruption and digital transformation, which shifted conventional employment patterns. In principle, gig economy workers have no formal working hours because their services can be widely accessed and used through the on-demand platform provided by a company. Their freedom to determine when, where, and how they work makes gig workers unable to be classified as employees, thus putting them in a precarious position without legal protection. This study aims to understand gig workers and platform provider companies' employment relationships, further defining the scheme of gig workers' legal protection. This study is a normative legal research with statutory and conceptual approaches, which are discussed using descriptive and argumentation methods. The study results show that according to the International Labour Organization's employment relationships classification, gig workers can be classified as a non-standard employment relationship in the form of dependent self-employment, which falls in a gray area between employee and independent contractor. The legal protection for gig workers can be accommodated by three different schemes, including expanding the concept of workers, defining a third category, and establishing independent legislation.